2018
DOI: 10.1038/s41598-018-32395-1
|View full text |Cite
|
Sign up to set email alerts
|

Printable all-dielectric water-based absorber

Abstract: The phase interplay between overlapping electric and magnetic dipoles of equal amplitude generated by exclusively alldielectric structures presents an intriguing paradigm in the manipulation of electromagnetic energy. Here, we offer a holistic implementation by proposing an additive manufacturing route and associated design principles that enable the programming and fabrication of synthetic multi-material microstructures. In turn, we compose, manufacture and experimentally validate the first demonstrable 3d pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…To maximize the scattering, the dipole resonance frequencies must overlap, but the fulfillment of the condition a 1 ¼ b 1 remains. Other larger element shapes satisfying Kerker's first condition exhibit greater scattering, but their sizes are also significantly larger [7,[13][14][15]. Using elements composed of both metal and water, it can be shown that the FBR can be enhanced as well as the total scattering efficiency.…”
Section: Configuration and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To maximize the scattering, the dipole resonance frequencies must overlap, but the fulfillment of the condition a 1 ¼ b 1 remains. Other larger element shapes satisfying Kerker's first condition exhibit greater scattering, but their sizes are also significantly larger [7,[13][14][15]. Using elements composed of both metal and water, it can be shown that the FBR can be enhanced as well as the total scattering efficiency.…”
Section: Configuration and Resultsmentioning
confidence: 99%
“…Both electric and magnetic dipoles can be excited in the sphere, but we pay most of our attention to the latter because it is the dominant mode. MSs with dielectric inclusions satisfying the first Kerker condition are currently of great interest [7,[13][14][15]. We demonstrate that this condition can also be satisfied in a water sphere, and we investigate how it is affected by the water losses.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…74) Other types of WB inclusions have been investigated including cylinders, 73 a water-metal hybrid structure, 79 and even more complex shapes. 47,59 Their fundamental electromagnetic properties display various performance characteristics providing a variety of options for the designing of WB devices composed of resonators.…”
Section: A Mie Resonances In Single Water Inclusionsmentioning
confidence: 99%
“…Recent researches demonstrate that metastructures possess uncommon properties in effectively improving the electromagnetic wave absorbing and shielding performance. [101][102][103][104][105][106][107][108][109][110] Metastructures with a complex 3D structure combine material loss and structural loss, which greatly improves the microwave absorbing properties. And thus, it is feasible to apply metastructures in numerous fields such as antenna technologies, radar, EMI shielding materials, and electromagnetic wave absorption materials.…”
Section: Introductionmentioning
confidence: 99%